Surface controlled reduction kinetics of nominally undoped polycrystalline CeO2. Issue 8 (28th February 2015) - Knoblauch, Nicole; Dörrer, Lars; Fielitz, Peter; Schmücker, Martin; Borchardt, Günter
<x xml:space="preserve">Abstract</x> The oxygen loss of nominally undoped dense polycrystalline ceria is monitored by thermogravimetric analyses. It is shown that the kinetics of oxygen release is surface controlled.